2010
DOI: 10.1007/s10517-010-1099-5
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Effects of Thioanalogs of Thrombin-Binding DNA-Aptamer and Their Stability in the Plasma

Abstract: In order to create effective therapeutically significant oligonucleotide structures, a series of analogs of thrombin-binding aptamer d(GGTTGGTGTGGTTGG) containing thiophosphoryl substitutions were synthesized. The anticoagulation effects of the resultant thrombin-binding aptamer analogs were evaluated and the effects of local thiomodifications on their structure and function were studied, including the effects on stability in blood plasma and resistance to DNA nucleases. A promising modified oligonucleotide (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…Thermodynamic studies reveal that, in general, the methylphosphonate analog eliminates negative backbone charges and thereby destabilizes the G-quadruplex structure while the phosphorothioate analog influences the thermal stability in a molecularity-dependent manner [43]. To improve the stability of the phosphodiester linkage in the thrombin aptamer, thiophosphoryl substitutions at different internucleotide sites were studied [44,45]. Since complete substitution by thiophosphorylated deoxyoligonucleotides was limited by its high toxicity [45], partially thiophosphorylated aptamers with maximum thermal stability were evaluated for their stabilities stability under the hydrolysis of RQ1 Dnase and their anti-thrombin activities in the anticoagulation of blood plasma [45].…”
Section: Modifications On Linkagementioning
confidence: 99%
See 1 more Smart Citation
“…Thermodynamic studies reveal that, in general, the methylphosphonate analog eliminates negative backbone charges and thereby destabilizes the G-quadruplex structure while the phosphorothioate analog influences the thermal stability in a molecularity-dependent manner [43]. To improve the stability of the phosphodiester linkage in the thrombin aptamer, thiophosphoryl substitutions at different internucleotide sites were studied [44,45]. Since complete substitution by thiophosphorylated deoxyoligonucleotides was limited by its high toxicity [45], partially thiophosphorylated aptamers with maximum thermal stability were evaluated for their stabilities stability under the hydrolysis of RQ1 Dnase and their anti-thrombin activities in the anticoagulation of blood plasma [45].…”
Section: Modifications On Linkagementioning
confidence: 99%
“…To improve the stability of the phosphodiester linkage in the thrombin aptamer, thiophosphoryl substitutions at different internucleotide sites were studied [44,45]. Since complete substitution by thiophosphorylated deoxyoligonucleotides was limited by its high toxicity [45], partially thiophosphorylated aptamers with maximum thermal stability were evaluated for their stabilities stability under the hydrolysis of RQ1 Dnase and their anti-thrombin activities in the anticoagulation of blood plasma [45]. Aptamer d(GG S T S T S GGTGTGG S T S T S GG) with thio-substitutions at loop regions exhibited similar anti-thrombin activity to originally unmodified ones but a three-fold better stability against nucleases in human blood serum [44] and a significantly slower hydrolysis rate in human plasma [45].…”
Section: Modifications On Linkagementioning
confidence: 99%
“…A significant number of chemically modified TBA analogs have been reported in the last decade [10], [11], [12], [13], [14], [15]. The relative benefits of those modifications are difficult to determine based on published data because very few modified aptamers have been comprehensively investigated.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that GQ formation is crucial for TBA binding with thrombin [10], [11], so modifications that decrease GQ thermostability (i.e. almost any substantial modification in the quadruplex core [11], [12], [13]) are undesirable. Loop modifications tend to have insignificant effects on quadruplex thermostability, but often impart increased nuclease resistance to the aptamer [11], [12], [13].…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have exploited non-natural modifications of the nucleobases (Krawczyk et al, 1995;He et al, 1998a;Marathias et al, 1999;López de la Osa et al, 2006;Mendelboum Raviv et al, 2008;Nallagatla et al, 2009;Goji & Matsui, 2011), which included: 1) guanines modified with hydrophobic substituents in the N 2 and C 8 positions; 2) 6-thio-, 3) 8-amino-, 4) iso-, and 5) 8-bromo-guanine modifications; and 6) thymine with 4-thio-uracil substitutions. Other research groups modified the nucleotide backbone of TBA 15 by introducing valuable surrogates replacing the natural phosphodiester linkages, such as: 1) neutral formacetal groups (He et al, 1998b), 2) phosphorothioate linkages (Saccà et al, 2005;Pozmogova et al, 2010;Zaitseva et al, 2010), 3) 3′-3′ or 5′-5′ phosphodiester bonds (Martino et al, 2006;Esposito et al, 2007;Pagano et al, 2008;Russo Krauss et al, 2011), and 4) methylphosphonate bonds (Saccà et al, 2005), or the nucleoside moieties, with insertion within the backbone of: 5) 2′-deoxy-2′-fluoro-D-arabinonucleotides (2′F-araN) (Peng & Damha, 2007), 6) locked-nucleic acids Bonifacio et al, 2008), 7) unlocked nucleic acids (UNA) (Agarwal et al, 2011;Jensen et al, 2011;Pasternak et al, 2011), and 8) acyclic thymine nucleoside (Coppola et al, 2008) residues. Most of these chemical modifications do not result into relevant improvements in the anticoagulant properties of TBA, even if in some reports an increase of the overall stability of the G-quadruplex structure and/or of the affinity for thrombin is registered.…”
Section: The Thrombin Binding Aptamers (Tbas)mentioning
confidence: 99%